2023
DOI: 10.2147/idr.s408572
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem Pharmacokinetics and Target Attainment in Critically Ill Patients

Abstract: Purpose This study aimed to investigate the pharmacokinetics and target attainment of meropenem and compare the effect of meropenem dosing regimens in critically ill patients. Patients and Methods Thirty-seven critically ill patients who were administered meropenem in intensive care units were analyzed. Patients were classified according to their renal function. Pharmacokinetic parameters were assessed based on Bayesian estimation. The target attainment of 40%fT > MIC (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In a separate evaluation of 47 critically ill adults treated with meropenem, a u-shaped curve existed where the poorest target attainment was observed in either patients with augmented renal clearance (i.e., estimated creatinine clearance [eCrCl] Cockcroft-Gault ≥ 130 mL/min) or in patients with severe renal insufficiency (i.e., eCrCl Cockcroft-Gault 15–29 mL/min) (30). Other studies have suggested that lower eGFRs were associated with improved target attainment (32, 33). In the present study of 51 critically ill patients, we reinforce the clear importance of GFR in the clearance of meropenem.…”
Section: Discussionmentioning
confidence: 95%
“…In a separate evaluation of 47 critically ill adults treated with meropenem, a u-shaped curve existed where the poorest target attainment was observed in either patients with augmented renal clearance (i.e., estimated creatinine clearance [eCrCl] Cockcroft-Gault ≥ 130 mL/min) or in patients with severe renal insufficiency (i.e., eCrCl Cockcroft-Gault 15–29 mL/min) (30). Other studies have suggested that lower eGFRs were associated with improved target attainment (32, 33). In the present study of 51 critically ill patients, we reinforce the clear importance of GFR in the clearance of meropenem.…”
Section: Discussionmentioning
confidence: 95%